2022
DOI: 10.3390/plants11233193
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Endemic Species Specialized in Island Habitat under Climate Change in a Mediterranean High Mountain

Abstract: Mediterranean high-mountain endemic species are particularly vulnerable to climatic changes in temperature, precipitation and snow-cover dynamics. Sierra Nevada (Spain) is a biodiversity hotspot in the western Mediterranean, with an enormous plant species richness and endemicity. Moehringia fontqueri is a threatened endemic plant restricted to north-facing siliceous rocks along a few ridges of the eastern Sierra Nevada. To guide conservation actions against climate change effects, here we propose the simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…This is compelling evidence that the cooler, wetter regions offer the optimal conditions for promoting new tree growth. In the same way, Mendoza-Fernández et al (2022) have shown that for Moehringia fontqueri Pau [now Arenaria suffruticosa Fior and P.O. Karis (cf.…”
Section: Conservation Statusmentioning
confidence: 74%
“…This is compelling evidence that the cooler, wetter regions offer the optimal conditions for promoting new tree growth. In the same way, Mendoza-Fernández et al (2022) have shown that for Moehringia fontqueri Pau [now Arenaria suffruticosa Fior and P.O. Karis (cf.…”
Section: Conservation Statusmentioning
confidence: 74%
“…High-elevation species are particularly vulnerable, as they exhibit lower photosynthetic acclimation to warmer temperatures than plants from lower elevations (Hernández-Fuentes et al, 2023). Similarly, endemics identi ed by various studies in the Mediterranean and Alpine ecosystems are particularly sensitive to climate change due to their small and fragmented populations, reducing habitat suitability and reproductive success (González-Mancebo, 2022; Mendoza-Fernández et al, 2022). Despite global studies on climate change effects, extensive research is urgently needed to understand the speci c impacts of climate change on the Peruvian Lomas ecosystem.…”
Section: The Lomas Ecosystemmentioning
confidence: 99%
“…The use of ENM contributes to define which are the most important areas to conserve or manage. For instance, Mendoza-Fernández et al (2022) found that populations found in low elevations were threatened and required conservation strategies when ecological niche models were adjusted at high elevations. In this sense, short-term measures must be taken in low-elevation areas rather than mountain summits, where habitat is supposed to be adequate in the future.…”
Section: In Situ and Ex Situ Management Applicationsmentioning
confidence: 99%